Secret of the water dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2015)
When Drake discovers that his friend and fellow Dragon Master, Bo, is trying to steal the Dragon Stone, he wonders if the dark wizard might be behind it, and he must try to find a way to protect the stone while keeping Bo's family out of danger.